2008
DOI: 10.1111/j.1523-1739.2007.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Disturbance of Tropical Forests on Frugivores and Seed Removal of a Small‐Seeded Afrotropical Tree

Abstract: Small-scale, local disturbance of tropical forests, for example from selective logging, is widespread, but its effects on biodiversity and ecosystem function have rarely been studied. In 3 East African tropical rainforests, we investigated the effect of different levels of local forest disturbance on the frugivore community and on tree visitation and fruit removal rates of the small-seeded tree Celtis durandii. We quantified birds and primates in little and heavily disturbed sites, distinguishing between fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 37 publications
5
93
5
2
Order By: Relevance
“…14); hunting also removes vertebrate seed predators and seedling browsers (20, 22, 23), making it difficult to isolate an effect of seed disperser loss alone; and the treatment of interest (removal of vertebrate dispersers) can be confounded with other site differences. Hunting pressure, for example, is often higher in areas without formal conservation protection, meaning these areas experience additional human pressures that affect tree populations, such as forest fragmentation and tree harvesting (14,20,24,25).Here, we exploit a unique situation, the loss of vertebrate dispersers on the island of Guam (Fig. 1) and their presence on the nearby islands of Saipan and Rota (8,26,27), to quantify the contribution of vertebrate seed dispersal to local species richness (alpha diversity) and spatial turnover (beta diversity) of tree seedlings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14); hunting also removes vertebrate seed predators and seedling browsers (20, 22, 23), making it difficult to isolate an effect of seed disperser loss alone; and the treatment of interest (removal of vertebrate dispersers) can be confounded with other site differences. Hunting pressure, for example, is often higher in areas without formal conservation protection, meaning these areas experience additional human pressures that affect tree populations, such as forest fragmentation and tree harvesting (14,20,24,25).Here, we exploit a unique situation, the loss of vertebrate dispersers on the island of Guam (Fig. 1) and their presence on the nearby islands of Saipan and Rota (8,26,27), to quantify the contribution of vertebrate seed dispersal to local species richness (alpha diversity) and spatial turnover (beta diversity) of tree seedlings.…”
mentioning
confidence: 99%
“…14); hunting also removes vertebrate seed predators and seedling browsers (20,22,23), making it difficult to isolate an effect of seed disperser loss alone; and the treatment of interest (removal of vertebrate dispersers) can be confounded with other site differences. Hunting pressure, for example, is often higher in areas without formal conservation protection, meaning these areas experience additional human pressures that affect tree populations, such as forest fragmentation and tree harvesting (14,20,24,25).…”
mentioning
confidence: 99%
“…Dysoxylum maoto and Dysoxylum samoensis, both indigenous to Samoa (Whistler 1994), are in peak fruit from January through September (Webb et al 1999). We recorded visitation and feeding based on scan sampling (Altmann 1974), a method used commonly to assess behaviour of both birds and fruit bats (Pitter and Christiansen 1997;Sun and Moermond 1997; Ochoa-Acuna and Kunz 1999;Munoz-Romo 2006), as well as to investigate visitation and feeding at focal trees (Boinski and Scott 1988;Tirado Herrera et al 2003;Kirika et al 2008). Observations at Erythrina focal trees were made between 05:00 and 09:00 to capture peak feeding times for most avian and fruit-bat species.…”
mentioning
confidence: 99%
“…For example, many frugivores require large fruiting trees as their main food source; they also represent a functionally important guild for the maintenance of plant diversity (Sekercioglu 2006;Kirika et al 2008). This agrees with past research in a tropical landscape that revealed a stronger response of specialist foraging guilds frugivores and insectivores to extent of secondary forest rather than habitat heterogeneity (De Bonilla et al 2012).…”
Section: Different Responses At Different Scalesmentioning
confidence: 99%
“…Examination of the response of richness within different foraging guilds to landscape properties would provide a useful basis for development of management plans (French and Picozzi 2002) particularly for disturbance-sensitive groups such as insectivores and frugivores (Kirika et al 2008). …”
Section: Components Of Diversitymentioning
confidence: 99%